International peace conference on Chittagong Hill Tracts : . Working towards peace : Bangkok declaration on peace in the CHT : International Peace Conference on Chittagong Hill Tracts 23-26 February 1997 Bangkok, Thailand (ACFOD, 1997)
Cover title: Working towards peace : Bangkok declaration on peace in the CHT : International Peace Conference on Chittagong Hill Tracts 23-26 February 1997 Bangkok, Thailand.